Surgical treatment of colorectal cancer liver metastases - ŠIMČIKAS, Dainius; PAŠKONIS, Marius; SOKOLOVAS, Vitalijus; POŠKUS, Eligijus; STRUPAS, Kęstutis (Acta medica Lituanica, 2011)
Background. Colorectal cancer is a major health problem. Approximately 25% of the patients present with liver metastases at initial diagnosis and more than 50% develop metastases in the course of illness. Over the last few decades, with improvements in therapy, the management of colorectal liver metastases has changed dramatically. In this review, we explore various current modalities of care, with surgical treatment ahead, for patients with colorectal liver metastases and present a brief report about the Vilnius University Hospital Santariskiu Clinics experience in the surgical treatment of metastatic liver disease.Methods. The Medline / PubMed literature database was searched for articles on the topics of colorectal liver metastases, including criteria of surgical resectability, chemotherapy, adjunctive and locoregional therapies. Also, results of the surgical treatment of liver metastases at the Vilnius University Hospital Santariskiu Clinics were analysed.Results. Globally, surgical liver resection for colorectal liver metastases remains the only regular curative treatment with the 5-year survival rates reported as 20–50%. With improvements in therapy, resectability criteria are expanding. Hepatic metastases are primarily resectable in 15–25% cases only. Up to 25% of patients with initially non-resectable metastases become amenable to a potentially curative operation after interdisciplinary treatment involving preoperative chemotherapy, portal vein embolization or ligation, few-stage hepatectomy, and / or locally ablative procedures. We observed good and optimistic survival results in the Vilnius University Hospital Santariskiu Clinics patient population after liver resection: 1-, 2- and 3-year survival was 86.9%, 63.5% and 42.3%, respectively.Conclusions. Over the last ten years, liver surgery has changed dramatically. A thorough selection of patients with colorectal liver metastases in a multidisciplinary team may improve treatment results significantly. Surgical treatment results for liver metastases at the Vilnius University Hospital Santariskiu Clinics are good.Keywords: colorectal liver metastases, liver resection, ablation, chemotherapy, portal vein embolisation